Halofuginone has a Beneficial Effect on Gentamicin-induced Acute Nephrotoxicity in Rats - ALİCAN, YAŞAR İNCİ (TAYLOR & FRANCIS LTD, 2009)
The aim of this study was to investigate the putative beneficial effect of halofuginone on gentamicin-induced nephrotoxicity in rats. Sprague-Dawley rats were treated with gentamicin sulphate (GEN; 80 mg/kg) or saline intraperitoneally (i.p.) for 7 days. Halofuginone was administered (0.1 mg/kg/day; i.p.) following GEN or saline injections. Blood and urine samples were collected to measure the renal function tests. Kidneys were excised for histological evaluation and for the measurement of malondialdehyde (MDA), glutathione (GSH), myeloperoxidase (MPO) activity, and chemiluminescence (CL). Halofuginone treatment to animals with GEN-induced renal injury caused a significant decrease in serum blood urea nitrogen level and reduced the elevated MDA, GSH content, and MPO activity. It was also effective in reversing the elevated CL values of rats with GEN-induced nephrotoxicity and preserving renal morphology, as examined microscopically. In conclusion, halofuginone was beneficial in GEN-induced acute nephrotoxicity. The mechanism could be attributed, at least in part, to decreased tissue leukocyte infiltration and reactive metabolite production.
Keywords: Gentamicin; halofuginone; nephrotoxicity; VERSUS-HOST-DISEASE; ACUTE-RENAL-FAILURE; COLLAGEN-SYNTHESIS; I SYNTHESIS; LIPID-PEROXIDATION; CELL-PROLIFERATION; FREE-RADICALS; INHIBITION; CARCINOMA; FIBROSIS